1987
DOI: 10.1055/s-2006-962810
|View full text |Cite
|
Sign up to set email alerts
|

Gansongon, ein neues Aristolan-Keton ausNardostachys chinensis Batalinund Strukturrevision eines Aristolenols

Abstract: A new instable aristolane type sesquiterpene ketone, gansongone ( 1), was isolated from the fresh underground parts of NARDOSTACHYS CHINESIS Batalin (Valerianaceae), growing in the province Sichuan (China). The structure of 1 was elucidated by spectroscopic and chemical methods. The structure of the corresponding alcohol 2, which was also found in N. CHINENSIS and formerly regarded as 9-aristolene-1alpha-ol ( 5) has to be revised to l(10)-aristolene-9beta-ol ( 2) from results of 2D-NMR-spectroscopy and oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The NOE correlations of the two methyl signals H-14 and H-15 with H-6 indicated that H-6 and the two methyls (C-14 and C-15) are on the same face of the ring system. The coupling constant between H-6 and H-7 (J = 9.2 Hz) implied the cis-orientation of H-6 and H-7 [15,16], which was also verified by the NOESY experiment. The small coupling constant for H-1 (J = 2.2 Hz) clearly established the Br functionality at C-1 to be in the α position.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The NOE correlations of the two methyl signals H-14 and H-15 with H-6 indicated that H-6 and the two methyls (C-14 and C-15) are on the same face of the ring system. The coupling constant between H-6 and H-7 (J = 9.2 Hz) implied the cis-orientation of H-6 and H-7 [15,16], which was also verified by the NOESY experiment. The small coupling constant for H-1 (J = 2.2 Hz) clearly established the Br functionality at C-1 to be in the α position.…”
Section: Resultssupporting
confidence: 58%
“…Since all 15 carbons were sp 3 hybridized as indicated by 13 C NMR and DEPT spectra (Table 1), the 4 degrees of unsaturation indicated the presence of a tetracyclic ring system in 1. The methine signal at δ C = 65.2 and the quaternary carbon signal at δ C = 66.5 were deduced to be those connected to the oxygen atom, and the methine signal resonating at δ C = 57.2 was ascribed to be brominated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, sesquiterpenes such as aristolene, â-maaliene, isonardosione, nardostachin, nardofuran, nardoquaianone (3,(20)(21)(22) have been reported in N. chinensis.…”
Section: Resultsmentioning
confidence: 84%
“…The structures of compounds 1-9 were determined to be aristolone (1) [3], 1(10)-aristolen-9E-ol (2) [4], 1(10),8-aristoladien-2-one (3) [5,6], aplysistatin (4) [7], 2,3,5,6-tetrabromo-1-methyl-1H-indole (5) [8], 2,3,5,6-tetrabromoindole (6) [9], 3,5,6-tribromo-1H-indole (7) [10], phytol (8) [7,11], and cholesterol (9) [12] on the basis of their 1 H NMR, 13 C NMR, and EI-MS spectral data and by comparison with those previously reported in the literature. Among these metabolites, compounds 1-7 were first isolated from C. papillosus.…”
mentioning
confidence: 99%